2018
DOI: 10.1177/1090198118762106
|View full text |Cite
|
Sign up to set email alerts
|

Physically Active Lessons Improve Lesson Activity and On-Task Behavior: A Cluster-Randomized Controlled Trial of the “Virtual Traveller” Intervention

Abstract: Abstract:Background: Physically active lessons have not often been assessed with randomised controlled trials. Aims: Evaluate the effects of the 'Virtual Traveller' intervention delivered using classroom interactive whiteboards on physical activity, on-task behaviour and student engagement. Methods: Participants were 219 children aged 8-9 years from ten schools in Greater London, assessed in a cluster-randomised controlled trial between March 2015 and May 2016. For six weeks, intervention children received 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 57 publications
5
28
0
3
Order By: Relevance
“…Interventions contained an average of 3. 18 or an audio CD and CD player 65 . Intervention effects on outcomes…”
Section: Behaviour Change Techniques (Bcts) Used In Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions contained an average of 3. 18 or an audio CD and CD player 65 . Intervention effects on outcomes…”
Section: Behaviour Change Techniques (Bcts) Used In Interventionsmentioning
confidence: 99%
“…13 14 Physically active lessons (also known as physically active learning 15 ) combine physical activity with academic content and have been explored as a potential method of increasing activity in schools without detriment to educational time. 16 Examples of physically active lessons include doing starjumps whilst reciting times tables 17 or using movements to show whether an answer is true or false 18 . Embedded physical activity can be specifically relevant to the learning task at-hand, or task non-relevant but still occurring simultaneously in the taught session 19 .…”
Section: Introductionmentioning
confidence: 99%
“…An evolving literature shows that PA in the classroom has the potential to contribute to the PA levels of children, in addition to the benefits on cognitive and academic outcomes [ 8 , 9 , 10 , 11 ], however, results remain inconclusive due to limited high quality interventions [ 12 ]. A number of intervention studies conducted in the academic classroom have also only assessed overall PA at school [ 13 , 14 , 15 , 16 ] or overall PA levels during the week [ 17 , 18 , 19 ]. To more objectively evaluate this approach it is important to directly capture activity levels at the classroom level.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the large number of classroom-based intervention studies that have been identified from recent reviews and meta-analyses [ 4 , 5 , 6 ], only 9 studies have objectively estimated the PA of lessons integrated with learning [ 13 , 14 , 15 , 16 , 18 , 20 , 21 , 22 , 23 ]. Of these, five compared the PA levels of the integrated lessons to a control group or condition [ 14 , 18 , 20 , 21 , 22 ], and only three provided detail on the actual intensity of the integrated activities [ 18 , 20 , 22 ]. The “Virtual Traveler” program [ 18 ] embedded Google earth videos on interactive whiteboards and children reached MVPA levels by simulating appropriate on-the-spot movements as they ‘traveled’ to, and interacted with, locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation